2021
DOI: 10.1101/2021.07.31.454562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ageing-associated myelin dysfunction drives amyloid deposition in mouse models of Alzheimer’s disease

Abstract: The prevalence of Alzheimer's disease (AD), the leading cause of dementia, shows a strict age-dependency, but why ageing constitutes the main risk factor for this disease is still poorly understood. Brain ageing affects oligodendrocytes and the structural integrity of myelin sheaths, the latter associated with secondary neuroinflammation. Since oligodendrocytes support axonal and neuronal health, we hypothesised that ageing-associated loss of myelin integrity could be an upstream risk factor for neuronal amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 80 publications
4
33
0
1
Order By: Relevance
“…The ON is a highly vascularized tissue In the absence of prior studies devoted to NVC in mammalian WM tracts, we focused on a well-known model system, the rodent optic nerve (ON). Using confocal and light-sheet microscopy with a modified iDisco clearing protocol (Depp et al, 2021), we revealed the 3D vessel-arrangement of the ON and annotated different populations of perivascular cells based on a recently proposed nomenclature for their morphology (Grant et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The ON is a highly vascularized tissue In the absence of prior studies devoted to NVC in mammalian WM tracts, we focused on a well-known model system, the rodent optic nerve (ON). Using confocal and light-sheet microscopy with a modified iDisco clearing protocol (Depp et al, 2021), we revealed the 3D vessel-arrangement of the ON and annotated different populations of perivascular cells based on a recently proposed nomenclature for their morphology (Grant et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Myelin damage has been observed previously in histochemical and neuroimaging studies in AD [38][39][40][41] , and recent single cell studies provide converging results showing that alterations in oligodendrocytes, a cell-type involved in myelination, are prominent in AD 42,43 . Recent studies in transgenic mouse models of amyloid pathology suggest that acute demyelination may occur upstream of amyloid deposition by interfering with a TREM2-related microglia activation signature, thus leading to enhanced amyloid deposition 44 . Thus, more vulnerable, thinner myelinated regions may engage in dysfunctional microglial activity resulting in less efficient removal of AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive myelin loss was observed in APP mice and in individuals with AD both by in vivo imaging as well as in histopathological studies [170][171][172]. Recent studies showed that myelin loss drives Aβ deposition, and that enhancing myelin renewal in turn alleviate the cognitive deficits in APP/PS1 mice [173] and in 5×FAD mice [174]. A number of studies have applied in vivo and ex vivo DTI for detecting the white matter impairment, which appears preceding the anatomical changes on structural MRI including the APPswe, APP/PS1, TgCRND8, APP NL-G-F , 3×Tg, CVN-AD and 5×FAD mice [81,93,97,175-183] (Table 3).…”
Section: Dtimentioning
confidence: 99%